The influence of state‐level policy environments on the activation of the Medicaid SBIRT reimbursement codes. (February 2017) - Hinde, Jesse; Bray, Jeremy; Kaiser, David; Mallonee, Erin; Del Boca, Frances K.; Babor, Thomas F.; Bray, Jeremy W.
Abstract: Aims: To examine how institutional constraints, comprising federal actions and states' substance abuse policy environments, influence states' decisions to activate Medicaid reimbursement codes for screening and brief intervention for risky substance use in the United States. Methods: A discrete‐time duration model was used to estimate the effect of institutional constraints on the likelihood of activating the Medicaid reimbursement codes. Primary constraints included federal Screening, Brief Intervention and Referral to Treatment (SBIRT) grant funding, substance abuse priority, economic climate, political climate and interstate diffusion. Study data came from publicly available secondary data sources. Results: Federal SBIRT grant funding did not affect significantly the likelihood of activation ( P  = 0.628). A $1 increase in per‐capita block grant funding was associated with a 10‐percentage point reduction in the likelihood of activation ( P  = 0.003) and a $1 increase in per‐capita state substance use disorder expenditures was associated with a 2‐percentage point increase in the likelihood of activation ( P  = 0.004). States with enacted parity laws ( P  = 0.016) and a Democratic‐controlled state government were also more likely to activate the codes. Conclusion: In the United States, the determinants of state activation of Medicaid Screening, Brief Intervention and Referral to Treatment (SBIRT) reimbursement codes are complex, and include more than financial considerations. Federal block grant funding is a strong disincentive to activating the SBIRT reimbursement codes, while more direct federal SBIRT grant funding has no detectable effects.